UTILIZING ARTIFICIAL INTELLIGENCE IN INVESTOR-STATE DISPUTE SETTLEMENT: PRESENT ISSUES AND FUTURE CHALLENGES - LU YAN,; TIE FATT HEE, (Journal of Malaysian and Comparative Law, 2025)
The integration of Artificial Intelligence (AI) into Investor-State Dispute Settlement (ISDS) has emerged as a transformative force, promising to streamline complex investor-state arbitration processes and enhance the accuracy of legal determinations. However, this technological advancement also presents several challenges, necessitating a critical examination of the role of AI in shaping the future of ISDS. This paper evaluates the impact of AI on ISDS, highlighting its potential to improve investor-state arbitration by enriching efficiency, objective decision-making, and advanced evidence analysis. It acknowledges the capacity of AI in refining risk assessment and predicts dispute outcomes, providing a cutting-edge approach to ISDS. However, the analysis also addresses significant concerns, including algorithmic bias, the ethical implications of decision-making, and the overreliance on technology that may overlook the complexity of human judgment. To overcome these challenges, the paper suggests a regulatory framework that mandates transparency and accountability, ensures justice through rigorous algorithm audits, and promotes a collaborative relationship between humans and AI. By maintaining human autonomy and enhancing the role of AI as an assistive tool, especially in intricate cases, the paper advocates for a balanced integration of AI in ISDS, striving for a harmonious blend of technological innovation and human expertise in future arbitration processes.